Determining pregnanediol in normal pregnancy and menstrual cycle - Guerra García, R. (2015)
The authors have studied the excretion of pregnanediol in 85 normal women by using the method of Sulimovici. During the menstrual cycle the mean values ± S.E. for 12 women were 1.0 ± 0 .15 and 3.65 ± 0 .33 mg./24 hr. for the proliferative and secretory phases respectively. The mean values in 63 pregnant women were 7.54 ± 0 .32, 9.19 ± 0.65, 8 .32 ± 0.67, 12.46 ± 0.88, 21.64 ± 0.8 and 28.37 ± 0.91 mg./g. creatinine for the months 2nd., 3rd., 4th., 5th., 7th. and 10th. The procedure was compared to Kloppers method and no differences were detected. As additional proof of the specificity of the method employed, the urine extracts were analyzed by gas-liquid chromatography and, pregnanediol was found to be the principal component of the final extract.